The proportion of bran and guava on the macro nutrition, fiber, and acceptability of ice cream - Durrotul Ma'sumah; Desty Muzarofatus Sholikhah; Sutrisno Adi Prayitno (Universitas Muhammadiyah Gresik, 2021)
The research objective was to determine the effect of the proportion of bran and guava on the levels of macro nutrition, fiber, acceptability, and the economic value of ice cream products, as well as being a snack for functional obese adolescents. The research method was experimental design with a completely randomized design consisting of 3 modified formulas (F1, F2, and F3) and 1 control formula tested on 42 panelists. Organoleptic were carried out by the Friedman test and advanced test Duncan's. Macro and fiber nutritional levels were obtained through laboratory tests and analyzed using the One Way Anova test continued Tukey test. The chemical test results for macronutrients and fiber showed a significant effect between the formula (0.00<0.05) and the macronutrients F0, F1, F2, F3, namely carbohydrates 32,70 g, 27,36 g, 2,78 g, 24,26 g, Protein 5,51 g, 7,30 g, 6,95 g, 6,19 g, fat 8,24 g, 6,01 g, 6,42 g, 6,76 g, fiber 0,86 g, 5,73 g, 5,30 g, 5,05 g. Organoleptic results (F0, F1, F2, F3) taste preferences 3,43, 3,26, 2,76, 2,31, aroma 2,98, 3,29, 2,90, 2,90, 2,55, color 3,24, 3,19, 3,21, 2,88, and texture 3,12, 3,14, 2,83, 2,71 , there is a significant treatment effect between the formula with the Chi-Square Asym.sig value <0.05 and the best formula is F1 with a mean rank of 39,5.